Romanian Local Action Groups’ (LAGs) Economic Impact: A Solution to a Problem or a Perpetuating Status Quo of a Gimmick? - Daniel Buda; Antonia Pop (Transylvanian Review of Administrative Sciences, 2024)
This article takes into consideration local action groups (LAGs) in the European Union and Romania in particular, in terms of resources needed, resources used, and measured impact on public services, infrastructures, and quality of life. Previous research showed that the impact of LAGs is difficult to assess due to weak links between actions and objectives and also due to different benchmarking. Romania absorbs EU funds for agriculture and rural development, however, the administrative, preparatory, and project costs are high, raising certain questions about LAGs’ genuine productivity and performance. This article provides clarity on LAGs’ costs and benefits, by mapping out a state of play of LAGs and comparing findings with expert opinions. Policy formulation and recommendations conclude this research.